Comparative study on outcome of surgical management of varicose veins with and without great saphenous vein stripping - Gourraj , Sanghamithra; Shastri, Sree Mounika; Anantha, Bhanu Prakash (International Surgery Journal, 2023)
Background: Varicose veins of lower limb are multiple elongated dilated and tortuous veins. It is a progressive disease that worsens as the day passes. The treatment modalities available are conservative, surgical and endovenous therapies. It is accepted that surgical treatment is required for symptomatic varicose veins, to relieve symptoms and to prevent the long-term sequelae of eczema, lipodermatosclerosis and venous ulceration. Different surgical interventions may be used, but most preferred treatment applied is saphenofemoral flush ligation and ligation of incompetent perforators. Methods: This prospective comparative study was conducted on 60 patients in the department of general surgery, Mamata general hospital from July 2020 to June 2022. 60 patients were allocated into two groups of 30 patients each, who underwent flush ligation of saphenofemoral junction with stripping of long saphenous varicose vein and Trendelenburg surgery alone (flush ligation of sapheno femoral junction) respectively. Results: The hematoma formation in the thigh was seen in 23.33% of patients who underwent venous stripping whereas it was seen only in 3.33% who underwent Trendelenburg procedure alone. These wounds were examined in the postoperative period. Delayed wound healing was observed in 26.66% in patients with venous stripping and it was 10% with Trendelenburg procedure alone. There was no significant difference in postoperative ambulation, hospital stay and pain relief after 2 months. Conclusions: From this study with the observed variables, it is concluded that the Trendelenburg procedure with incompetent perforators ligation without venous stripping appears to be better than Trendelenburg procedure with incompetent perforators ligation with venous stripping.